Business Intelligence: Oxymoron or a Big Data Technique? - Latta, Michael (Journal of Applied Business and Economics, 2018)
Business education current practice prepares students for analysis with tools such as Strengths, Weaknesses, Opportunity, and Threats (SWOT Analysis). Predictive Analytics and Data Science coupled with Big Data are popular. As faculty show students how to help business organizations solve real-world problems with these advanced analysis tools, they need to understand how to integrate the softer side of Business Intelligence into business analysis practice. These softer skills include Knowledge from Education, Practical IQ, Emotional IQ and Interpersonal IQ. Taken together they define Business Intelligence which is highly useful in both academic assignments like internships and on the job after graduation.